On the species of the genus Anthaxia Eschscholtz, 1829 described by A. Théry from Angola in 1947 (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2015)
The type specimens of the genus Anthaxia Eschscholtz, 1829 described from Angola by A. Théry (1947) were studied, critically evaluated and some of them synonymised: Anthaxia (Cratomerus) reticollis Quedenfeldt, 1886 = A. (C.) coelestis Théry, 1947, syn. nov., A. (Haplanthaxia) egena Kerremans, 1913 = A. (H.) decimata Théry, 1947, syn. nov., A. (H.) duvivieri Kerremans, 1898 = A. (H.) eumede Théry, 1947, syn. nov., A. (H.) mashuna Obenberger, 1931 = A. (H.) morula Théry, 1947, syn. nov. and A. (H.) sjoestedti Kerremans, 1908 = A. (H.) recisa Théry, 1947, syn. nov. The male of A. (H.) monardi Théry, 1947 is briefly described and A. (H.) puchneri Bílý, 2014 is shortly discussed. All mentioned species and the relevant types of the newly synonymised species are illustrated.